PENGARUH PERBEDAAN DOSIS OKSIGEN TERLARUT (DO) PADA DEGRADASI AMONIUM KOLAM KAJIAN BUDIDAYA UDANG - Komarawidjaja, Wage (Jurnal Hidrosfir Indonesia, 2006)
The objective of the study is to determine the effectiveness of bacterial application and various continuous dissolved oxygen (DO) treatment for nitrogen (ammonia, nitrite and nitrate) degradation in shrimp culture. The DO treatment was set as 4.5 mg/L for treatment-I, 5.5 mg/L for treatment-II and 6.5 mg/L for treatment-III. The batch oxidation was conducted for a period of 20 days. The temperature, pH, salinitas, DO, ammonia, nitrite and nitrate were determined.Based on some previous research papers. NH3 becomes toxic to shrimp if the concentration is higher than 0.54mg/Lr. NH3 measurement on this experiment was about 0.01 mg/L up to 2.5 mg/L, but frequently was found lower than 0.54 mg/L in the pond under treatment-III (6.5 mg/L DO).The result also indicates that nitrification process in the experiment pond was not only depend on DO level and abundance of nitrifier, but also was influenced by a possibility of the occurrence of organic compound that inhibit nitrification.